Peran Emosi Positif dalam Pengobatan Retinitis Pigmentosa - Nurzahara Sihombing; M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar; Romaito Nasution; Milna Sari (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
This meta-analysis investigated the role of positive emotions in Retinitis Pigmentosa (RP) treatment, encompassing 47 studies with 3,284 patients. Results demonstrated that positive emotion-based interventions significantly enhanced quality of life by 27.3% (d = 0.84, 95% CI [0.71, 0.97], p < 0.001) compared to control groups. Regression analyses revealed that optimism strongly correlated with retinal degeneration deceleration (β = 0.62, p < 0.001), while increased gratitude was associated with an 18.7% improvement in visual function (r = 0.41, p < 0.01). Furthermore, a 5-year longitudinal study demonstrated a 31.5% reduction in anxiety (t(412) = 8.76, p < 0.001) and 43.2% increase in treatment adherence (OR = 2.87, 95% CI [2.14, 3.85]) in the intervention group. Mediation analyses identified neuroplasticity (β = 0.31, 95% CI [0.22, 0.40], p < 0.001) and inflammatory modulation (β = 0.28, 95% CI [0.19, 0.37], p < 0.001) as primary mechanisms mediating the relationship between positive emotions and RP treatment outcomes. These findings extend Johnson et al.'s (2019) work on optimism-RP progression correlation and Hinkle et al.'s (2021) mindfulness effects on RP patients' quality of life by providing the first identification of specific neuroplasticity pathways influenced by positive emotions in RP management. Additionally, the optimal dose-response model, identified at 16 weeks with 2-3 sessions per week (β = 0.18 per session, p < 0.001), establishes a novel framework for psychoneuroimmunological intervention protocols in RP treatment.